Adaptive response in stress granule formation and bulk translational repression upon a combined stress of mild heat shock and mild ethanol stress in yeast. (30th August 2013) - Yamamoto, Yosuke; Izawa, Shingo
Abstract : The formation of cytoplasmic mRNA–protein complex granules termed 'processing bodies and stress granules' is often induced in the stress responses of eukaryotic cells. Most previous studies on stress granules have focused on the response to a single type of stress, and little information is available about the response to combined stress. Additionally, the effects of adaptation on stress granule formation and bulk translation activity are poorly understood. We investigated the formation of stress granules upon combined exposure to mild heat shock (37 °C) and mild ethanol stress (5% v/v) in Saccharomyces cerevisiae . Although neither stress alone induced stress granule formation, their combination caused a pronounced repression of translation activity and the formation of stress granules. Pretreatment with each mild stress significantly attenuated the formation of stress granules and caused changes in the composition of stress granules upon the subsequent combined stress and facilitated stress granule disassembly accompanied by smooth translational resurrection during the recovery process, indicating that yeast cells can induce adaptations in stress granule formation. However, the pretreated cells still exhibited a severe repression of translation activity. These findings provide novel and fundamental insight into the regulation of yeast stress granules.